Satu Saudara: Pelaksanaan Pendidikan Multikultural di TK X Kabupaten Jember - Husnah, Ifrohatul; Wardhani, Wahju Dyah Laksmi; Adwitiya, Asti Bhawika (Jurnal Pendidikan Anak Usia Dini, 2023)
Indonesia is a country rich in diversity, encompassing various ethnicities, religions, races, and languages, which necessitates its citizens to cultivate a spirit of tolerance towards one another. One effective means of fostering an understanding of diversity is through multicultural education. Multicultural education is especially important when applied to children from a young age, as it equips them to approach differences with acceptance and a sense of tolerance in the future. The aim of this research is to describe the implementation of multicultural education in one of the preschools in Jember Regency, where students exhibit different religious characteristics. The research methodology employed in this study is qualitative, involving data collection through methods such as observation, interviews, and documentation. The findings of this research indicate that, in response to the religious diversity present within the school, the institution packages multicultural education in the form of a flagship program called "One Brotherhood," held annually. In its implementation, teachers divide students according to their respective religions, which include Christians, Catholics, Muslims, Buddhists, and Hindus. Furthermore, the "One Brotherhood" program includes a tolerance class that serves as a bridge to reinforce religious tolerance among young children.